AN ANALYTICAL APPROACH TO THE IMPLICIT EXPRESSION OF MEANING IN LITERARY TEXTS (World Bulletin of Social Sciences, 2025)
The article explores the implicit expression of meaning in literary texts. It provides an analytical approach to various types of hidden meanings in the Uzbek language, such as conveying concealed ideas through imagery, expressing implicit meaning through dialogues, and using symbols and metaphors. The study analyzes the implicit expression of meaning based on the works of the writer Odil Yoqubov
Keywords: Literary text; implicit expression